Publisher Correction: Chlorophyll f synthesis by a super-rogue photosystem II complex - Trinugroho, Joko P; Bečková, Martina; Shao, Shengxi; Yu, Jianfeng; Zhao, Ziyu; Murray, James W; Sobotka, Roman; Komenda, Josef; Nixon, Peter J (Nature plants, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.